Resources of the Russian Financial Market - K. E. Manuylov (Vestnik MGIMO-Universiteta)
The article highlights the basic factors, defining the amount of resources available at Russian financial market, as well as the causes of long-term capital deficit. Special attention is drawn to analysis of monetary policy of the Central bank of Russian Federation, which has had a major impact on capital supply at the national financial market in recent years.